Respuesta :

Answer:

Answer for #10:

[tex]y = 2 \: and \: x = 1[/tex]

Answer for #1:

[tex]x = 2 \: and \: y = - 1[/tex]

Step-by-step explanation:

In order to solve a simultaneous equation using the substitution method you have to:

Use one of the equation and substitute it into the other equation, in this case equation B was substituted into equation A.

[tex]equ. \: a = (2x - 3y = 7) \\ equ. \: b = (x = 1 - y)[/tex]

Therefore since x = 1 - y, equation A would be:

[tex]2(1 - y) - 3y = 7 \\ (2 - 2y) - 3y = 7 \\ - 2y - 3y = 7 - 2 \\ - 5y = 5 \\ y = - 1 \: and \: x = 2[/tex]